2014
DOI: 10.3171/2014.7.peds1431
|View full text |Cite
|
Sign up to set email alerts
|

Development of a de novo arteriovenous malformation after severe traumatic brain injury

Abstract: Arteriovenous malformations (AVMs) are typically considered congenital lesions, although there is growing evidence for de novo formation of these lesions as well. The authors present the case of an AVM in the same cerebral cortex that had been affected by a severe traumatic brain injury (TBI) more than 6 years earlier. To the best of the authors' knowledge, this is the first report attributing the formation of an AVM directly to TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…27 Case reports have been documented since. 13,633 The findings support the concept that the process of AVM formation is multifactorial and is related to congenital, environmental and haemodynamic factors. 2,5 De novo AVM risk factors noted included a history of haemorrhage, ischaemic stroke, radiation exposure, familial AVMs and aneurysm, dural arteriovenous fistula, Moyamoya disease or cavernoma on initial diagnosis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…27 Case reports have been documented since. 13,633 The findings support the concept that the process of AVM formation is multifactorial and is related to congenital, environmental and haemodynamic factors. 2,5 De novo AVM risk factors noted included a history of haemorrhage, ischaemic stroke, radiation exposure, familial AVMs and aneurysm, dural arteriovenous fistula, Moyamoya disease or cavernoma on initial diagnosis.…”
Section: Discussionsupporting
confidence: 78%
“…2,5 De novo AVM risk factors noted included a history of haemorrhage, ischaemic stroke, radiation exposure, familial AVMs and aneurysm, dural arteriovenous fistula, Moyamoya disease or cavernoma on initial diagnosis. [1][2][3] 11 1 Haemorrhage DSA Haemorrhage Temporal NA Morioka 21 1 Haemorrhage DSA Seizure Frontal III Fuse 9 1 Haemorrhage DSA Incidental Frontal II Rodríguez-Arias 27 1 Right parietal AVM DSA Incidental Parietal III Harris 4 1 Anaplastic astrocytoma DSA Incidental Thalamus III Jeffree 12 3 16 1 Medulloblastoma MRI Incidental Sylvian fissure I Miyasaka 19 1 Haematoma DSA Haemorrhage Multiple cerebral AVMs NA Friedman 7 1 Dural arteriovenous fistula MRI, DSA Incidental NA NA Nakamura 22 1 Haemorrhage MRI, DSA Haemorrhage Frontal II Shidoh 30 1 Aneurysm MRI, DSA Incidental Postcentral gyrus II Pabaney 26 1 18 1 TBI, surgery MRI New-onset seizures Parietal I Kilbourn 13 1 Congenital hydrocephalus CT, MRI Haemorrhage Brainstem IV Fujimura 8 1 Moyamoya disease MRI Incidental Occipital II Bai 3 1 Cerebral arteriovenous fistula MRI, DSA New-onset seizures Frontal I Alvarez 2 1 Giant cavernoma MRI Incidental Third ventricle III Mahajan 15 1 Bell's palsy MRI New-onset seizures Frontoparietal III Ozsarac 25 1 There are no papers addressing the subsequent clinical behaviour of these lesions. An unanswered clinical question is whether the behaviour of a de novo AVM is similar to that of an initially discovered AVM.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other studies have suggested that brain AVMs are caused by an abnormal response to injuries as a result of trauma or radiation [8][9][10] . Likewise, the exact mechanism of TAC development in AVM patients is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for brain AVM development have been discussed in the literature, but these discussions are few in number, especially ones that discuss TAC in superficial AVMs [5][6][7][8][9][10] . The most common and widely recognized clinical features of AVMs are seizures, headaches and neurological deficits related to intracere-bral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…In 21 cases 2,12, [14][15][16][17]19,20,[22][23][24][28][29][30][31] , reported de novo AVM was reported in patients that had another vascular pathology, such as prior resection of an AVM in a different brain location during childhood, previous hemorrhagic stroke or intracranial aneurysm. The majority of the cases (n=19) were pediatric 11,[15][16][17][18][19][20][21][22][23][24][25][26]31 and only 9 involved young adult patients (<35 years old) 2,5,7,9,10,13,14,27,29 .…”
Section: Case Reportmentioning
confidence: 99%